Los Regímenes Tributarios y su impacto en la carga fiscal de los contribuyentes de Ecuador, período 2024. - Balseca Méndez, Bryan Alexis (2025)
The current research aimed to analyze the impact of the tax regimes in force on the tax burden of taxpayers in Ecuador during 2024. The study employed a mixed-methods, correlational approach using the hypothetical-deductive method. A questionnaire was administered to a sample of 384 active taxpayers from the General Regime, the RIMPE Entrepreneur Regime, and the RIMPE Popular Business Regime. The results evidenced a statistically significant relationship between belonging to a specific regime and the perception of the tax burden (p < 0.001), thereby allowing rejection of the Null Hypothesis. The main conclusion was that the RIMPE Popular Business's fixed-rate design compromises the system's Vertical Equity, as low-capacity taxpayers perceive a disproportionate burden. It is recommended that the SRI revise the presumptive rates to ensure progressivity.